Towards secure identity management for the smart grid. Issue 9 (3rd April 2014) - Baumeister, Todd; Dong, Yingfei
Abstract: The emerging smart grid incorporates modern information systems with traditional power delivery systems to achieve better control, efficiency, and reliability. However, it also brings potential cyber security risks into the essential power system. Therefore, we need a large‐scale framework to address the basic security issues such as identity management in the smart grid. While public key infrastructures (PKIs) have been developed for large‐scale distributed information systems, the existing PKI solutions cannot meet the unique requirements of the electrical power grid. In this paper, we first identify those unique requirements and discuss how the existing PKI trust models may be adapted to meet these requirements; we further evaluate the existing certificate revocation models; we then discuss various PKI adaptations for the smart grid. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : The emerging smart grid incorporates modern information systems with traditional power delivery systems to achieve better control, efficiency, and reliability. However, it also brings potential cyber security risks into the essential power system. Therefore, we need a large‐scale framework to address the basic security issues such as identity management in the smart grid. While public key infrastructures (PKIs) have been developed for large‐scale distributed information systems, the existing PKI solutions cannot meet the unique requirements of the electrical power grid.